Palmitic acid differently modulates extracellular vesicles and cellular fatty acid composition of SGBS adipocytes without impairing their insulin signaling - Sergi, Domenico; Angelini, Sharon; Castaldo, Fabiola; Beccaria, Marco; Bellinghieri, Carlo; Franchina, Flavio; Omenetto, Alice; Stifani, Gabriella; Del Mastro, Sefora; Merighi, Stefania; Gessi, Stefania; Jugdaohsingh, Ravin; et al. (Frontiers in Endocrinology, 2025)
ScopeAdipocyte-derived extracellular vesicle (EV) lipid cargo reflects the obese metabolic state. Nevertheless, it is currently unknown whether the adipocyte-derived EV lipid profile is influenced by saturated fatty acid overload. This study investigated if palmitic acid (PA) affected human Simpson–Golabi–Behmel syndrome (SGBS) adipocyte insulin sensitivity and the repercussions on the EV fatty acid cargo secreted by these cells.MethodsAdipocytes were treated with 500 or 1,000 μM of PA, and cytotoxicity was assessed using the lactate dehydrogenase assay. Thereafter, cells were treated with 1,000 μM of PA for 48 h, followed by the assessment of triglyceride accumulation and adipokine expression. Insulin signaling, NF-κβ activation, and stearoyl-CoA desaturase-1 (SCD) abundance were assessed by Western blot. EVs were isolated via ultracentrifugation, and the intracellular as well as the EV fatty acid profile was characterized using gas chromatography coupled to a flame ionization detector.ResultsNeither 500 nor 1,000 μM of PA did not elicited a cytotoxic effect on SGBS adipocytes. PA promoted adipocyte hypertrophy without hampering insulin signaling or triggering the activation of NF-κβ. However, PA increased intracellular and EV SFA content and raised intracellular oleic acid (OA) levels in parallel with the upregulation of SCD, while it decreased OA content in EVs.ConclusionsActive lipid sorting within EVs may be an additional mechanism underpinning intercellular communication by which adipocytes inform other cells about their metabolic status. However, further studies are warranted to evaluate the effects of EV lipid cargo on recipient cells.